The Applicability of Cash Waqf Linked Sukuk (CWLS) Through the Tafriqus Sufqah Al-Khatib Al-Sharbini Theory: An Approach to Sharia Compliance and Financial Innovation - Abidah, Atik; Asnawi, Nur; Suprayitno, Eko; Zuhriah, Erfaniah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This research article delves into the examination of Cash Waqf Linked Sukuk (CWLS) within the framework of Islamic jurisprudence, particularly through the lens of Al-Khatib Al-Sharbini's Tafriqus Sufqah theory. Utilizing the guidance provided by the Fatwa DSN-MUI No. 131/DSN-MUI/X/2019, this study aims to scrutinize the Shariah compliance of CWLS, a contemporary Islamic financial instrument that amalgamates the concept of waqf (Islamic endowment) with sukuk (Islamic bonds), to foster economic and social development projects. The primary objective is to understand how CWLS adheres to Shariah principles by dissecting its structure and operations into separate contracts or agreements, in alignment with Tafriqus Sufqah theory, which advocates for clarity and segregation in financial dealings to avoid ambiguity (gharar), gambling (maysir), and interest (riba). Through qualitative analysis of the fatwa and relevant Islamic financial literature, the study explores the theoretical underpinnings of CWLS, evaluates its compliance with Islamic law, and assesses its innovative approach to integrating charitable giving with financial investments. The findings aim to contribute to the Islamic finance literature by offering insights on the application of Tafriqus Sufqah theory to modern financial instruments like CWLS, highlighting its potential for ethical investment and the challenges of ensuring Shariah compliance. This analysis not only enriches the understanding of Islamic financial products but also provides a model for developing future Shariah-compliant instruments that can meet the needs of contemporary Muslim societies.